Flotação por ar dissolvido para os minerais quartzo e feldspato utilizando coletores catiônicos - Barbalho, Bruno Castro (2012)
The pegmatite rocks in Rio Grande do Norte are responsible for much of the production of industrial minerals like quartz and feldspar. Quartz and feldspar are minerals from pegmatite which may occur in pockets with metric to centimetric dimensions or as millimetric to sub millimetric intergrowths. The correct physical liberation of the mineral of interest, in case of intergrowths, requires an appropriate particle size, acquired by size reduction operations. The method for treating mineral which has a high efficiency fines particles recovery is flotation. The main purpose of the present study is to evaluate the recovery of quartz and potassium feldspar using cationic diamine and quaternary ammonium salt as collectors by means of dissolved air flotation DAF. The tests were performed based on a central composite design 24, by which the influence of process variables was statistically verified: concentration of the quaternary ammonium salt and diamine collectors, pH and conditioning time. The efficiency of flotation was calculated from the removal of turbidity of the solution. Results of maximum flotation efficiency (60%) were found in the level curves, plotted in conditions of low concentrations of collectors (1,0 x 10-5 mol.L-1). These high flotation efficiencies were obtained when operating at pH 4 to 8 with conditioning time ranging from 3 to 5 minutes. Thus, the results showed that the process variables have played important roles in the dissolved air flotation process concerning the flotability of the minerals.